Computed Tomography–Based Imaging of Voxel-Wise Lesion Water Uptake in Ischemic Brain: Relationship Between Density and Direct Volumetry. Issue 4 (April 2018) - Broocks, Gabriel; Flottmann, Fabian; Ernst, Marielle; Faizy, Tobias Djamsched; Minnerup, Jens; Siemonsen, Susanne; Fiehler, Jens; Kemmling, Andre
Abstract : Objectives: Net water uptake per volume of brain tissue may be calculated by computed tomography (CT) density, and this imaging biomarker has recently been investigated as a predictor of lesion age in acute stroke. However, the hypothesis that measurements of CT density may be used to quantify net water uptake per volume of infarct lesion has not been validated by direct volumetric measurements so far. The purpose of this study was to (1) develop a theoretical relationship between CT density reduction and net water uptake per volume of ischemic lesions and (2) confirm this relationship by quantitative in vitro and in vivo CT image analysis using direct volumetric measurements. Materials and Methods: We developed a theoretical rationale for a linear relationship between net water uptake per volume of ischemic lesions and CT attenuation. The derived relationship between water uptake and CT density was tested in vitro in a set of increasingly diluted iodine solutions with successive CT measurements. Furthermore, the consistency of this relationship was evaluated using human in vivo CT images in a retrospective multicentric cohort. In 50 edematous infarct lesions, net water uptake was determined by direct measurement of the volumetric difference between the ischemic and normal hemisphere and was correlated with net water uptake calculated by ischemic density measurements. Results: With regard to in vitro data, water uptake by density measurement was equivalent to direct volumetric measurement ( r = 0.99, P < 0.0001; mean ± SD difference, −0.29% ± 0.39%, not different from 0, P < 0.0001). In the study cohort, the mean ± SD uptake of water within infarct measured by volumetry was 44.7 ± 26.8 mL and the mean percent water uptake per lesion volume was 22.7% ± 7.4%. This was equivalent to percent water uptake obtained from density measurements: 21.4% ± 6.4%. The mean difference between percent water uptake by direct volumetry and percent water uptake by CT density was −1.79% ± 3.40%, which was not significantly different from 0 ( P < 0.0001). Conclusions: Volume of water uptake in infarct lesions can be calculated quantitatively by relative CT density measurements. Voxel-wise imaging of water uptake depicts lesion pathophysiology and could serve as a quantitative imaging biomarker of acute infarct lesions. Abstract : Supplemental digital content is available in the text.